Diagnostic value of planar myocardial perfusion scintigraphy in patients with coronary artery disease - Klančič, Marko (Radiology and oncology (Ljubljana), 1997)
Patients with suspected or proven coronary artery disease are investigated using noninvasive and invasive diagnostic methods. Noninvasive myocardial perfusion scintigraphy provides data on myocardial perfusion during stress andat rest. Coronary angiography is invasive morphologic method, performed before coronary artery dilatation or surgery. Aim of our retrograde analysis of planar thallium myocardial perfusion scintigrams and coronary angiograms was to assess sensitivity and specificity of rnyocardial perfusion planar scanning and to evaluate causes of possible disagreement. Original readings ofmyocardial perfusion scans and coronary angiograms of 156 patients with coronary artery disease were compared. When results of both investigations were partially concordant or discordant, the original studies were reviewed. Concordant results of both examinations were found in 62% of patients. In only3% (5 patierrts) the results were discordant and the reason for disagreement of results of both studies could not be detected. Most of the remaining 55 patients had more pronounced myocardial perfusion defects than was the estinrated severity of cororsary artery stenosis, attributed to the different nature of both irtvestigations. Anonralous coronary artery was foundirt 3% of all patients, tortuous coronary arteries with slow ftow of coritrast media in 9 patients (6% of all) and arterial hypertension with extreme left ventricular wall hypertrophy in one patient. Serrsitivity of the rnyocardial perfusion scintigraphy was l00% and specificity 50%. Positive predictive valrre for coronary artery disease was 96% and negative predictive value was 100 %. We cconclude that myocardial perfusion scintigraphy has a definite role in: diagnosis and follow-up of patients with suspected or provencoronary artery disease. (Abstracts truncated at 2000 characters)
Keywords: diagnostika; koronarna bolezen; srčne bolezni